2003
DOI: 10.1163/156854103769224368
|View full text |Cite
|
Sign up to set email alerts
|

Heterorhabditis baujardi sp. n. (Rhabditida: Heterorhabditidae) from Vietnam and morphometric data for H. indica populations

Abstract: A survey of entomopathogenic nematodes in Vietnam yielded several Heterorhabditis isolates. The majority belonged to H. indica; their morphometrics are given in this paper. Three isolates collected in forests in Backan, Ninhbinh and Kontum provinces, Vietnam are here described as a new species Heterorhabditis baujardi sp. n. The new species is distinguished from the other ten valid Heterorhabditis species by a combination of morphological, morphometrical, and DNA characters. Heterorhabditis baujardi sp. n. is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 24 publications
1
16
2
Order By: Relevance
“…These nucleotide variations were not present in the rest of H. bacteriophora member of the clade B. Results obtained in our study are according to Adams et al (1998) andPhan et al (2003) who analyzing DNA sequences of the ITS1 of the Heterorhabditis genus, showed the type strain H. bacteriophora (HB1) differing from H. argentinensis in a single transversion (G vs. C) at position 620 (Adams et al, 1998;Phan et al, 2003) and in a single insertion of a C at position 348 as we mentioned (Phan et al, 2003). Therefore, by the results obtained in our study, H. argentinensis would be a sister taxa of H. bacteriophora, as was considered by Adams et al (1998).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These nucleotide variations were not present in the rest of H. bacteriophora member of the clade B. Results obtained in our study are according to Adams et al (1998) andPhan et al (2003) who analyzing DNA sequences of the ITS1 of the Heterorhabditis genus, showed the type strain H. bacteriophora (HB1) differing from H. argentinensis in a single transversion (G vs. C) at position 620 (Adams et al, 1998;Phan et al, 2003) and in a single insertion of a C at position 348 as we mentioned (Phan et al, 2003). Therefore, by the results obtained in our study, H. argentinensis would be a sister taxa of H. bacteriophora, as was considered by Adams et al (1998).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, morphometric variations were observed according to Nguyen (2016) which considered some morphological features as highly variables for Argentinian strains. The greatest differences were registered between H. argentinensis and all other H. bacteriophora populations, unlike between H. bacteriophora strains from different regions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For ML analysis, the appropriate substitution model of DNA evolution that best fitted the data set was determined by the Akaike Information Criterion with Model Test 3.06 (Posada & Crandall, 1998). Bootstrap analysis with 1000 replicates was conducted as a measure of support for individual clades for MP and ML trees (Phan et al, 2003).…”
Section: Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%